Greening the Switch - Ananthanarayanan, Ganesh; Katz, Randy H. (USENIX HotPower, 2008)
Active research is being conducted in reducing power consumption of all the components of the Internet. To that end, we propose schemes for power reduction in network switches − Time Window Prediction, Power Save Mode and Lightweight Alternative. These schemes are adaptive to changing traffic patterns and automatically tune their parameters to guarantee a bounded and specified increase in latency. We propose a novel architecture for buffering ingress packets using shadow ports. We test our schemes on packet traces obtained from an enterprise network, and evaluate them using realistic power models for the switches. Our simple power reduction schemes produce power savings of up to 32% with minimal increase in latency or packet-loss. With appropriate hardware support in the form of Wake-on-Packet, shadow ports and fast transitioning of the ports between its high and low power states, these savings reach 90% of the optimal algorithm’s savings.